An Android-Based Vocabulary Model For Autism - Riyan Maulana; Bahruni B (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
>The characteristics of autistic children that tend to focus on their world encourage the writer to conduct this research. Their communication weaknesses have become a problem that faced by parents and teachers. This fact is reasonable because autistic children often create their own ways to communicate, such as using a word that has unique meaning for them or by making their own words to convey their needs or convey their intentions. The development of the world of technology and information is considered solve the learning problems for autism community, especially to improve the mastery of a foreign language (English language). An Android-based learning software/ application or learning model create for autistic children is one of examples that the author believe can help autistic students in their communication skills through a special language learning media or method that based on mobile learning / android app. A learning innovation that aims to help communication / improve foreign language mastery in this case vocabulary for autism children is one of the language learning innovations that want to be designed through this research as a guide or learning guide for them because autistic children prefer to do something based on their own way with a media or tool that have responsive value to attracts their attention.